Effectiveness of Modified Empty Palm Oil Bunch-Based Activated Carbon for Reducing Ammonia Content in Palm Oil Wastewater - Khairahmi; Ramadhan, Dwi Sapri; Faradilla, Putri; Rahmah, Siti; Selly, Rini; Jasmidi; Zubir, Moondra (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Indonesia, particularly North Sumatra, is a major producer of palm oil, generating significant waste such as empty fruit bunches (EFB) and ammonia-rich wastewater. Ammonia pollution poses serious environmental risks if not treated properly. This study explores the potential of three types of adsorbents—Fe-Cu modified activated carbon, AC-Cu(TAC)₂ composite, and unmodified activated carbon—for ammonia adsorption. Activated carbon was synthesized from EFB and further modified using Fe-Cu and Cu(TAC)₂. Adsorption experiments were conducted with variations in adsorbent mass, contact time, and NH₄OH concentration. The results showed that Fe-Cu modified activated carbon had the highest ammonia removal efficiency (90%), while the AC-Cu(TAC)₂ composite had the highest adsorption capacity. Equilibrium analysis revealed that the AC-Cu(TAC)₂ composite fit both Langmuir and Freundlich isotherm models (R² = 1), suggesting both monolayer and heterogeneous adsorption. The unmodified activated carbon followed the Langmuir model (R² = 0.9498), while Fe-Cu modified activated carbon did not fit either model. Kinetic studies indicated that Fe-Cu modified activated carbon followed a pseudo-first-order model (R² = 0.9936), implying physisorption, whereas both AC-Cu(TAC)₂ and unmodified activated carbon followed pseudo-second-order models (R² = 0.9779 and 0.9869), indicating chemisorption. These findings highlight the promising potential of modified EFB-based adsorbents for ammonia removal in wastewater treatment applications.